(untitled) (San Francisco, 2004)
This book should be read and acted upon by all higher educators who are trying to improve the academic performance, success, satisfaction, retention, and ultimate graduation rate of first-year students."
Keywords: Information literacy,Education, higher,Academic libraries,Kí tự thông tin,Giáo dục cao,Thư viện hàn lâm; Study and teaching ( higher ),Curricula,Relations with faculty and curriculum,Nghiên cứu và giảng dạy,Chương trình giảng dạy,Quan hệ với các giảng viên và chương trình giảng dạy; United States,United States,United States,Hoa Kỳ,Hoa Kỳ,Hoa Kỳ